The effects of internal and external imagery on performing figures in figure skating. - Mumford, B.; Hall, C. (Canadian Journal of Applied Sport Sciences, 1985)
Figure skaters (N = 59) were randomly assigned to four groups and performed a modified version of a senior-level figure. Each group performed a variation of imagery: (a) internal kinesthetic imagery, (b) internal visual imagery, (c) external visual imagery, and (d) no imagery (control). After four training sessions there were no differences in performance between the four groups. This might have been an artifact of the experimental design for such a format assumes that all groups will learn at the same rate. Four trials might not have been sufficient for "new" imagery skills to be developed effectively. However, an analysis of other comparisons and subject groupings revealed some interesting findings. 1. Senior skaters showed greater performance improvements and were superior kinesthetic imagers. 2. All Ss were similar on visual imagery skill but seniors were superior on kinesthetic imagery. 3. Imagery training increased skater confidence. Implication: In this study there is a suggestion of a relationship between imagery ability and motor learning. Better kinesthetic imagers seemed to perform in a superior fashion and learn faster. Kinesthetic imagery, as opposed to visual imagery, could be a better form of imagery for learning and performing motor skills.